GEODETIC WORKS IN BRIDGE CONSTRUCTION (Synergy: Cross-Disciplinary Journal of Digital Investigation (2995-4827), 2024)
A bridge is an engineering structure built to cross an obstacle (river, canal, ravine or other places). According to its function, the bridge is designed for automobile, railway and pedestrian. Bridge, overpass; instead of being built on city bridges and roads outside the city; combined (built together for automobiles and railways), according to the material used, wood, stone, metal, depending on the reinforced concrete bridge, prolyot systems, girder, arched and suspended, console; according to the number of prolyots, single-prolyot and multi-prolyot; according to their location in relation to the load-carrying structure, to types that move over, from below, from the middle; depending on the continuous and continuous traffic, the bridge is divided into permanent and movable (opening, lifting, sliding) types; It is divided into types that can be assembled and disassembled. There will also be a bridge-canal and bridge-houses. These act as bridges as well as houses and canals. In the past, bridges were mostly made of wood and stone. Old wooden bridges are not preserved.